Rahn And Wakalah Agreements From The Perspective Of Muamalah Law - Rahmanda Yusuf Nasution; Faizs Kurniawan; Muhammad Nur Iqbal (SEAN Institute, 2025)
Pawn in Islam is called with pawn . Pawn is a activity pawn goods as guarantee to a transaction debt incurred .​ Someone who pawns a the goods said ( rahin ) to then , then goods the still become owned by giver guarantee ( rahin ). As a result a recipient guarantee ( murtahin ) no may use or sell goods guarantee the before get permission from party giver guarantee . human , a object , a set of conditions , a system of thought or a class current events​​ Study This use method study law bibliography , namely research that done with method researching ingredients library or secondary data . The data sources used includes primary data such as the Criminal Code and data secondary in the form of design laws , results research , and opinions expert law . Data collection techniques are carried out through studies literature with collect data from various source reading written . Data analysis was carried out with use technique qualitative data analysis For processing research data . In jurisprudence muamalah and KHES, pawn called with rahn . While inside​ law civil pawn called with pand . Please often We hear Good in Sharia economy and in Islamic financial institutions . This is in the banking world there is in form services . In general public lay No so understand What do you mean with meaning of the word . The State of Indonesia whose State Foundation is Almighty God and the majority inhabitant his country is Muslim Already the financial system that should be used based on Sharia principles . However , when This Sharia principles have not so realized its use . Wakalah in the form of handover or delegation from One party to the other party and must done with what has been agreed by the mandate giver.